PENGUMPULAN DAN BATAS PEMAKAIAN SAMPEL POPOK PADA PERBENIHAN URIN - Rini Riyanti; Prihatini Prihatini; M.Y Probohoesodo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
Urinary tract infection diagnosis is based on urine culture, taken from a midstream collection in the morning. Obtaining samplesin this manner is difficult in children less than 3 years. In children less than 3 years, urine is obtained by urine collectors. Using urinecollectors may cause discomfort, and the possibility that the urine collectors may not adhere resulting in contamination. (1) Developinga practical method for urine sample collection. (2) Comparing culture from diapers and urine collectors samples. (3) Knowing the limittime for using diapers acceptable for urine culture. Urine samples were obtained from 20 children less than 3 years, using urine collectorsand diapers used for 1 hour, 2 hours and 3 hours and then cultured. Majority of the urine culture from diapers used for 1 hour and 2hours showed the same result with the urine culture from urine collectors. Contamination was found in the urine culture result fromdiapers used for 3 hours. Urine samples from diapers used for 1 hour and 2 hours can be used as samples for urine culture. The techniqueis easy and can be done in children less than 3 years.